Handbook on Business Process Management 2 (Strategic Alignment, Governance, People and Culture) - Brocke, Jan Vom (Springer, 2015)
Business Process Management (BPM) has emerged as a comprehensive consolida tion of disciplines sharing the belief that a process-centered approach leads to substantial improvements in both performance and compliance of a system. Apart from productivity gains, BPM has the power to innovate and continuously transform businesses and entire cross-organizational value chains. The paradigm of “process thinking” is by no means an invention of the last two decades but had already been postulated by early economists such as Adam Smith or engineers such as Frederick Taylor...